Flow Theory in Classrooms : a Study of How Homework Affects Learning. - Frie, Mark (My University, 2009)
This study involved using student surveys to look at the correlation between the two main flow variables, skill and concentration, as well as correlations with other variables that are indirectly related with flow. Specific case studies of movement between the flow categories from week to week were also analyzed. A few major results are the significant correlations between interest and challenge and between challenge and concentration.
Achieving Flow in Mathematics.
Color poster with text, charts, and graphs describing research conducted by Mark Frie, advised by Chistopher S. Hlas.
Keywords: Learning, Psychology of; Ability--Psychological aspects; Concentration (Psychology); Homework--Psychological aspects; Mathematics--Study and teaching; Study skills--Psychological aspects; Posters